Patient-Derived Bone Marrow Spheroids Reveal Leukemia-Initiating Cells Supported by Mesenchymal Hypoxic Niches in Pediatric B-ALL - Balandrán, Juan Carlos; Dávila-Velderrain, José; Sandoval-Cabrera, Antonio; Zamora-Herrera, Gabriela; Terán-Cerqueda, Vanessa; García-Stivalet, Lilia Adela; Limón-Flores, José Alejandro; Armenta-Castro, Erick; Rodríguez-Martínez, Aurora; Leon-Chavez, Bertha Alicia; Vallejo-Ruiz, Verónica; Hassane, Duane C.; et al. (Frontiers in Immunology, 2021)
B-cell acute lymphoblastic leukemia (B-ALL) results from the expansion of malignant lymphoid precursors within the bone marrow (BM), where hematopoietic niches and microenvironmental signals provide leukemia-initiating cells (LICs) the conditions to survive, proliferate, initiate disease, and relapse. Normal and malignant lymphopoiesis are highly dependent on the BM microenvironment, particularly on CXCL12-abundant Reticular (CAR) cells which provide a niche for maintenance of primitive cells. During B-ALL, leukemic cells hijack BM niches creating a proinflammatory milieu incompetent to support normal hematopoiesis but favoring leukemic proliferation. Although the lack of a phenotypic stem cell hierarchy is apparent in B-ALL, LICs are a rare and quiescent population potentially responsible for chemoresistance and relapse. Here, we developed novel patient-derived leukemia spheroids (PDLS), an ex vivo avatar model, from mesenchymal stromal cells (MSCs) and primary B-ALL cells, to mimic specialized niche structures and cell-to-cell intercommunication promoting normal and malignant hematopoiesis in pediatric B-ALL. 3D MSCs spheroids can recapitulate a CAR niche-like hypoxic structures that produce high levels of CXCL10 and CXCL11. We found that PDLS were preferentially enriched with leukemia cells displaying functional properties of LICs, such as quiescence, low reactive oxygen species, drug resistance, high engraftment in immunodeficient mice and long-term leukemogenesis. Moreover, the combination of PDLS and patient-derived xenografts confirmed a microenvironment-driven hierarchy in their leukemic potential. Importantly, transcriptional profiles of MSCs derived from primary patient samples revealed two unique signatures, (1) a CXCL12low inflammatory and leukemia expansion (ILE)-like niche, that likely supports leukemic burden, and (2) a CXCL11hi immune-suppressive and leukemia initiating cell (SLIC)-like niche, where LICs are likely sustained. Interestingly, the CXCL11+ hypoxic zones were recapitulated within the PDLS that are capable of supporting LICs functions. Taken together, we have implemented a novel PDLS system that enriches and supports leukemia cells with stem cell features driven by CXCL11+ MSCs within hypoxic microenvironments capable of recapitulating key features, such as tumor reemergence after exposure to chemotherapy and tumor initiation. This system represents a unique opportunity for designing ex vivo personalized avatars for B-ALL patients to evaluate their own LICs pathobiology and drug sensitivity in the context of the tumor microenvironment.